Computational simulation of a diesel generator consuming vegetable oil "in nature" and air enriched with hydrogen (2015)
A diesel generator was simulated operating with palm oil as fuel and hydrogen doping the inlet air. The objective was to investigate how the addition of hydrogen can accelerate the end of vegetable oil combustion, and consequently improve the electrical efficiency of the generator set up, for the same mass flow rate of fuel. The simulations were performed using AVL BOOST software and validated with experimental data. The generator was simulated operating with 75%, 80% and 100% of the nominal load using palm oil in nature, and hydrogen being injected at the intake manifold in parcels of 5% to a maximum of 20% in energy content by replacing the main fuel. The simulations showed increase in electrical power, reduction in specific fuel consumption, improving the overall efficiency of the generator set with 100% load. Good results were obtained with operation at 75% of the nominal load.